Efektifitas Penggunaan Media Pembelajaran Flashcard dalam Meningkatkan Kosakata Bahasa Inggris Siswa Kelas 2 SDN Karawaci 5 - Zulaini, Rizki; Cendany, Nafisa Nuarista; Ningrum, Gilang Kusuma (Lembaga Yasin AlSys, 2023)
English is referred to as the second language after Indonesian, because English is the language of instruction used internationally. therefore English is very necessary for students to equip them in facing global challenges and as a supporting tool in their lives. However, there are still many students who have difficulty mastering and understanding English vocabulary in supporting learning activities. Because there is still a lack of use of learning media in the process of learning activities, especially in learning vocabulary in English. This has an impact on the lack of understanding and mastery of vocabulary because learning takes place without any supporting media.One of the learning media that can be used in the effectiveness of learning English vocabulary is with Flash Card learning media. The purpose of this study was to determine the effectiveness of using flashcard learning media to improve English vocabulary mastery in class 2 of SDN Karawaci 5. The research method used was classroom action research (PTK) in which there were several stages as follows: planning ), implementation of the action (acting), observation (observation), and reflection (reflecting). And the data collection techniques used in this study consist of: tests, interviews, and observations. So the results obtained from this research in the first meeting had not achieved maximum results, at the first meeting it was seen that students were unable to pronounce vocabulary or understand vocabulary in English and even at this time students still looked confused in using Flash card learning media . And in the first cycle students get an average score of 68 with a learning completeness percentage of around 72%. By looking at the predetermined minimum completeness criteria (KKM) at SD Negeri Karawaci 5, namely 75, there were 13 people who reached the completion criteria. Which means only 72% while according to KTSP a lesson is said to be complete if the completeness score obtained by students is approximately 75% of the number of students. And in the second cycle there was an increase with an average value of 80, with learning completeness around 100%.